Determination of 23 Metal Elements in Detailed Soil Survey Samples by Inductively Coupled Plasma-Mass Spectrometry with Three Acid Stepwise Digestion - LIU Xiang-lei; SUN Wen-jun; WEN Tian-yao; LI Yong-xin; WANG Teng-fei; LIU Xue-li; YAN Yu; LI Huai-chao (Yankuang ceshi, 2020)
OBJECTIVES The soil detailed survey samples have the characteristics of large quantity, complex matrix, and high organic matter content. The traditional digestion method using a variety of mixed acid systems not only leads to incomplete digestion of organic matter, but also leaves black carbon in the solution after digestion. Because the sample is only extracted with dilute nitric acid, some insoluble oxides, sulfates, and fluorides are difficult to form soluble salts, resulting in incomplete extraction. If the reverse aqua regia is used during extraction, it is easy to introduce a large amount of chloride ions and cause the interference problem of chlorine multi-atomic ion mass spectrometry. OBJECTIVES In order to accurately determine 23 metal elements in soil. The analysis efficiency and quality can be improved by making full use of the different characteristics of nitric acid, hydrofluoric acid and perchloric acid in sample digestion. METHODS Soil samples were digested on electric heating plate, by stepwise addition of nitric acid, hydrofluoric acid and perchloric acid. For the digested samples, nitric acid-hydrochloric acid (20:1, V/V) mixed solution was used as the extractant, effectively reducing the interference of chlorine polyatomic ion mass spectrum and extracting elements thoroughly. Twenty-three metal elements in the soil were simultaneously determined by inductively coupled plasma-mass spectrometry (ICP-MS). RESULTS This method can effectively digest organic matter and silicate components in soil. It has the advantages of less reagent consumption, less mass spectrum interference of chlorine, simple operation process, high working efficiency, and lower detection limit (0.0008-0.90mg/kg, 3s). This method was applied to the national level standard substance such as dark brown soil, limestone soil, yellow brown soil samples for the determination of 23 elements, and the measurement result was superior to the traditional digestion method. The precision (RSD, n=6) was 0.022%-5.83% and relative error was -8.33% to 9.17%. The results are consistent with the certified values, indicating that the method is applicable and reliable. CONCLUSIONS The method for the simultaneous determination of 23 elements in soil samples by ICP-MS with three acid stepwise digestion has high applicability and reliability.